Perancangan Interior Showroom Mobil Mitsubishi Di Surabaya - Jap Jimmy Susanto; Filipus Priyo Suprobo (Intra, 2017)
The current four-wheeled Mitsubishi vehicles from japan are less know by the citizens in Surabaya. One of the reasons is the existence of many other car brands that are more popular and the monotonous design of the interior showroom.The influence also led to a decrease in sales of Mitsubishi showroom. To resolve this problem required a design that is different from the other four-wheeled vehicle brands is required. Interior design showroom Mitshubishi in Surabaya presents futuristic design style that is combined with GEO OPENERS concept that will make a difference and is unique in Surabaya.Transparent material is mostly used in public areas for visitors to make it look more open spaced, and comfortable for visitors and staffs. Mitsubishi showroom design begins with the creation of Programming obtained from survey results and interviews directly to the owner of the branch manager of the showroom, then continued with the creation of schematic and final design, followed by the creation of schematic design, and later continued with the creation of the final design.